Popularization of IPM Practices for Management of Chickpea Pod Borer, through Frontline Demonstrations under Semi Arid Conditions (Indian Journal of Extension Education, 2016)
The present study was conducted to popularize the IPM practices for the management of chickpea pod borer through frontline demonstrations in Panchmahals district of Central Gujarat. Constraints in chickpea production were identified through participatory approach. Preferential ranking technique was utilized to identify the constraints faced by the farmers in chickpea production. The results revealed that Helicoverpa armigera (Hubner) was the dominant chickpea constraint ranked first followed by lack of knowledge about IPM (rank 2) and Agrotis ipsilon (rank 3). Fusarium wilt (Fusarium oxysporum f sp ciceri) occupied the fourth rank. The extent of yield losses in chickpea were due to biotic stresses, viz. H. armigera, Agrotis ipsilon, Fusarium wilt and stored grain insect pests was reported by the farmers. On the basis of Rank Based Quotient (RBQ) and Value Based Index (VBI), it was found that H. armigera (VBI = 2303) is a major threat to chickpea causing highest damage to the crop. Results indicate that IPM practices, application of bio-pesticides i.e., HaNPVand neem oil revealed the best performance reduction in pod damage. The yield of chickpea in IPM practice was 17.55 q/ha as compared to farmers practices (13.75 q/ha). The percentage increase in yield over farmer’s practices was computed to be 27.64. Results of study on economic analysis of the yield performance revealed that the IPM practices recorded higher gross returns (` 43,875/ha) and net return (` 21,075/ha) with higher benefit cost ratio (1.92) as compared to farmer’s practices (1.62). Mean difference with respect to farmers’ knowledge level after implementation of frontline demonstrations increased to the tune of 33.13. The impact of frontline demonstrations was also analyzed which reflected significant improvement in knowledge and satisfaction level on the part of farmers. Frontline demonstrations brings out that the IPM practice is feasible and economically viable over farmers practice and is a better option to manage chickpea pod borer using eco-friendly measures.